Samples : from the patient to the laboratory : the impact of preanalytical variables on the quality of laboratory results - Guder, Walter G. (Weinheim ; [New York] : Wiley-VCH, 1996)
CD-ROM contains WHO regulations and recommendations. Compilation of findings from the literature and those obtained in practice on the use of anti coagulants and provides a list of analytes containing the available data on reference intervals, biological hal-life times, stability and influence and interference factors.
One CD-ROM in pocket attached to inside back cover entitled The quality of diagnostic samples.
Previous ed.: Darmstadt : GIT VERLAG, 2001.
Includes bibliographical references and index.
System requirements for accompanying CD-ROM: Microsoft Windows (Windows 95/98/ME/2000); at least 8 MB RAM (16 MB or more is recommended); 5 MB of free hard disk space; VGA card with feature connector and high resolution color monitor set up for video resolution 800 x 600, 32768 colors; Microsoft or IBM PS/2 mouse. Screen Display Settings:This Atlas requires a display of at least 256 colors (recommended 32768 colors). You may need to adjust your display settings to achieve the best results when viewing photos on this Atlas.
Keywords: Diagnosis, Laboratory -- Handbooks, manuals. etc; Diagnosis, Laboratory -- Methodology; Nursing -- Handbooks, manuals. etc